Cover Picture and Issue Information. (6th April 2018) - Unknown
Abstract : Cover image: One of the model organisms, the limpet, Patella vulgata, grazing its habitat on a rocky shore in Northern Ireland. Credit: C.J. Reddin. The mean and variance of ecological variables are dependent on sampling attributes such as the coverage of environmental heterogeneity (sampling extent) and spatial scale. Trophic niche width is often approximated by bulk tissue stable isotopes of C and N, that is, the population isotopic niche. However, recent studies suggest that environmental heterogeneity (experienced by individuals) may be more important in defining the isotopic niche width than trophic variability (see paper by Reddin et al., pp. 904–915 ).